Reinforcement Method for Transmission Corridor to Enhance Resilience Against Typhoon Disasters - Shanshan SHI; Xinchi WEI; Zijun YUAN; Haozhong CHENG; Yun SU; Heng ZHANG (Zhongguo dianli)
Identification and reinforcement of critical transmission corridors is an effective measure for power systems to defend against extreme disasters, such as typhoon. Therefore, a two-stage reinforcement method for disaster resilience enhancement is proposed. Firstly, key corridor identification indices, including weighted grid entropy and flow transfer entropy, are introduced based on complex network theory and system state analysis. Secondly, the Batts typhoon model is used to compute real-time wind speeds, followed by Monte Carlo sampling of corridor availability under different wind speeds, generating failure scenarios for transmission corridor reinforcement. On this basis, a two-stage transmission corridor reinforcement method is proposed. Stage 1 aims to minimize the sum of costs such as reinforcement and load loss, considering measures like corridor reinforcement and generator output adjustment. Stage 2 takes into account the integrity of the grid topology, further optimizing the transmission corridor reinforcement strategy with the goal of power accessibility. The study shows that the proposed method integrates both the topology and changes in system state, thus achieving the accurate identification of critical corridors and enhancing system resilience.